Sustainable Seafood Processing: Reducing Waste and Environmental Impact in Aquatic Ecosystems - Ore Areche, Franklin (2024)
The global seafood industry is crucial in food production, providing essential nutrition and contributing to food security. Beyond its traditional role, the industry holds significant potential for generating high-value products by utilizing seafood resources. This comprehensive review explores the diverse applications of seafood resources, focusing on fish, shellfish, and seaweeds, in producing high-value products. The review examines various technological processes in extracting and purifying bioactive compounds from seafood, highlighting the advancements in seafood processing areas such as nanoencapsulation, fermentation, and enzymatic hydrolysis. Furthermore, it also discusses these innovations' economic and environmental impacts, emphasizing the importance of sustainability and efficiency in utilizing seafood by-products and waste. The seafood industry can minimize environmental pollution and promote circular economy principles by repurposing these materials. The review provides a holistic view of the future directions in this field, advocating for continued research and development efforts to enhance the value and sustainability of seafood resources. Overall, this review underscores the significance of seafood-derived high-value products in addressing global challenges while fostering economic growth and environmental stewardship